2021
DOI: 10.1002/adhm.202102017
|View full text |Cite
|
Sign up to set email alerts
|

A Glutathione Activatable Photosensitizer for Combined Photodynamic and Gas Therapy under Red Light Irradiation

Abstract: Although photodynamic therapy (PDT) is a promising approach for cancer therapy, most existing photosensitizers lack selectivity for tumor cells and the overexpressed glutathione (GSH) in tumor cells reduces the PDT efficiency. Therefore, designing photosensitizers that can be selectively activated within tumor cells and combine PDT with other therapeutic modalities represents a route for precise and efficient anticancer treatment. Herein, an organic activatable photosensitizer, CyI-DNBS, bearing 2,4-dinitroben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…As shown in Figure 1G, the test paper lightened when exposed to the mixture of P-DOA NPs and Cys in a time-and concentration-dependent manner, indicating that P-DOA NPs can react with thiols to produce SO 2 . [38,43] In addition to the release of SO 2 , the reaction of DOA with thiol molecules (GSH or Cys) will also generate ALA (Scheme S2, Supporting Information). Thus, the release behavior of ALA from P-DOA NPs was then tested.…”
Section: Preparation and Characterization Of P-doa Npsmentioning
confidence: 99%
“…As shown in Figure 1G, the test paper lightened when exposed to the mixture of P-DOA NPs and Cys in a time-and concentration-dependent manner, indicating that P-DOA NPs can react with thiols to produce SO 2 . [38,43] In addition to the release of SO 2 , the reaction of DOA with thiol molecules (GSH or Cys) will also generate ALA (Scheme S2, Supporting Information). Thus, the release behavior of ALA from P-DOA NPs was then tested.…”
Section: Preparation and Characterization Of P-doa Npsmentioning
confidence: 99%
“…Cancer is currently one of the most common causes of death worldwide. To effectively treat cancer, researchers have tried a variety of treatments including gene therapy, chemotherapy, , radiotherapy, , and gas therapy. As an emerging treatment, gas therapy uses gas transmitters to induce tumor cell death. Studies have found that several gas molecules, such as nitric oxide (NO), carbon monoxide (CO), oxygen (O 2 ), and hydrogen sulfide (H 2 S), could regulate the process of cancer. Among them, NO was the first found gaseous biochemical messenger, and it played a dual role in tumor progression: low concentrations of NO might promote tumor growth, while high concentrations of NO (>1 μM) could induce tumor cell apoptosis through multiple pathways .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that photothermal-mediated heating will increase the blood flow and combination with photothermal therapy is regarded to enhance PDT inhibition of hypoxic tumors ( Wu et al, 2019a ; Chen et al, 2022 ). Benefiting from the unique characteristics of multifunctional nanomaterials, multiple therapeutic strategies can be simultaneously mediated by one nanoplatform to synergistically inhibit tumor, such as the combination of gas therapy ( Wan et al, 2018 ; Wang et al, 2022b ) and chemotherapy ( Yang et al, 2019a ; Wang et al, 2019e ), etc., Recently, some emerging nanomaterials such as heterojunction-based nanoparticles have been prepared to enhance the generation efficacy of ROS through catalytic reaction, deriving a new therapeutic strategy termed catalytic therapy. The combination of PDT and catalytic therapy implied a promising strategy to strengthen the therapeutic efficiency ( Pan et al, 2019 ; Kang et al, 2021 ; Kong et al, 2021 ; Pan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%